Addressing Decision Making in Progesterone Treatment for History of Preterm Delivery [27C]. (May 2018) - Zuponcic, Jacqueline; Lavin, Justin; Cottrell, Connie; Li, Marissa
Abstract : INTRODUCTION: The United States infant mortality rate of 6.1 deaths per 1000 live births ranks 27th worldwide. The majority of perinatal morbidity and mortality is related to preterm birth, whose only FDA approved preventive treatment is intramuscular 17-hydroxyprogesterone (17-OH-P) from 16-36 weeks of gestation. Unfortunately, many patients refuse this treatment. METHODS: This 12 month prospective study utilized a short survey, in combination with focus groups, to identify social, cultural, and personal reasoning that influences patients' decisions to accept or reject 17-OH-P treatment. We hypothesized that treatment refusal is multifactorial for any given patient. RESULTS: Acceptors (n=43) and refusals (n=7) were unable to generate sufficient power to identify statistically significant intragroup differences. However, utilizing these surveys and resultant focus groups, this study was able to identify trends within these populations which may guide future approaches to them. Patients refusing 17-OH-P often cited pain with injection, exhibited fatalistic beliefs regarding their care, and/or had personal concerns related to full term pregnancy. Acceptors were identified as candidates at the time of their previous preterm birth, coped better with treatment side effects, and/or had traumatic emotional reactions regarding their premature birth outcomes. Both groups cited barriers to their care–specifically including access and disparities within their care. CONCLUSION: Identifying these differences between women accepting and rejecting 17-OH-P may help to develop new approaches to improve patient acceptance of 17-OH-P therapy.